Insights into Titan's geology and hydrology based on enhanced image processing of Cassini RADAR data. Issue 10 (6th October 2014) - Lucas, Antoine; Aharonson, Oded; Deledalle, Charles; Hayes, Alexander G.; Kirk, Randolph; Howington‐Kraus, Elpitha
Abstract The Cassini Synthetic Aperture Radar has been acquiring images of Titan's surface since October 2004. To date, 59% of Titan's surface has been imaged by radar, with significant regions imaged more than once. Radar data suffer from speckle noise hindering interpretation of small‐scale features and comparison of reimaged regions for change detection. We present here a new image analysis technique that combines a denoising algorithm with mapping and quantitative measurements that greatly enhance the utility of the data and offers previously unattainable insights. After validating the technique, we demonstrate the potential improvement in understanding of surface processes on Titan and defining global mapping units, focusing on specific landforms including lakes, dunes, mountains, and fluvial features. Lake shorelines are delineated with greater accuracy. Previously unrecognized dissection by fluvial channels emerges beneath shallow methane cover. Dune wavelengths and interdune extents are more precisely measured. A significant refinement in producing digital elevation models is shown. Interactions of fluvial and aeolian processes with topographic relief is more precisely observed and understood than previously. Benches in bathymetry are observed in northern sea Ligeia Mare. Submerged valleys show similar depth suggesting that they are equilibrated with marine benches. These new observations suggest a liquid level increase in the northern sea, which may be due to changes on seasonal or longer timescales.